2000
DOI: 10.1093/milmed/165.7.539
|View full text |Cite
|
Sign up to set email alerts
|

Demographic, Lifestyle, and Psychosocial Predictors of Frequency of Intoxication and Other Indicators as Estimates of Alcohol-Related Problems in Air Force Basic Military Recruits

Abstract: This study examined demographic, lifestyle, and psychosocial variables to determine predictors of Air Force recruits who are likely to have alcohol-related problems. Subjects were all Air Force recruits (N = 32,144) entering basic training from August 1995 to September 1996. The dependent measures were self-reported frequency of eight or more drinks per occasion, frequency of fighting while drinking, and typical frequency of alcohol consumption. Demographic analysis revealed that individuals high on any depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Moreover, stress fractures of the cancellous bone may be a warning sign of early onset of osteopenia (Marx et al, 2001). Nearly one in five individuals in the military reports having engaged in heavy drinking, and college athletes, despite repetitive athlete-targeted anti-alcohol education campaigns, are more likely to drink than their nonathlete counterparts (Hunter et al, 2000;Nelson and Wechsler, 2001). These populations are regularly involved in endurance exercise, and their propensity for alcohol consumption presents a bone environment that has yet to be explored.…”
mentioning
confidence: 99%
“…Moreover, stress fractures of the cancellous bone may be a warning sign of early onset of osteopenia (Marx et al, 2001). Nearly one in five individuals in the military reports having engaged in heavy drinking, and college athletes, despite repetitive athlete-targeted anti-alcohol education campaigns, are more likely to drink than their nonathlete counterparts (Hunter et al, 2000;Nelson and Wechsler, 2001). These populations are regularly involved in endurance exercise, and their propensity for alcohol consumption presents a bone environment that has yet to be explored.…”
mentioning
confidence: 99%
“…Compared to their light-drinking peers, heavy drinkers responding to the Department of Defense Worldwide Survey exhibited a greater relative risk for exhibiting several work-related productivity losses (i.e., self-reported lateness, leaving early, low performance, and on-the-job injury). 32 Hunter et al 33 contend that high-risk drinking falls into a broader risk behavior category for military personnel. Specifically, among a sample ( n = 32,144) of Air Force recruits entering basic training, the frequency of consuming eight or more drinks per occasion, frequency of fighting while drinking, and typical frequency of drinking were linked to positive rebellious and risk-taking attitudes and increased likelihood of engaging in risky behaviors such as decreased seat belt use.…”
Section: Discussionmentioning
confidence: 99%
“…One report indicated that one out of 5 active US military personnel drank to excess [9]. A similar study in the UK found that 67% of men and 49% of women in the regular UK Armed Forces were engaged in “hazardous drinking” [10,11].…”
Section: Discussionmentioning
confidence: 99%